Economic evaluation of micafungin vs. Liposomal Amphotericin B (LAmB) for the treatment of candidaemia and Invasive Candidiasis (IC). Issue 5 (18th March 2013) - Neoh, Chin Fen; Liew, Danny; Slavin, Monica A.; Marriott, Debbie; Chen, Sharon C.‐A.; Morrissey, Orla; Stewart, Kay; Kong, David C. M.
Summary Micafungin was non‐inferior to liposomal amphotericin B (LAmB) for the treatment of candidaemia and invasive candidiasis (IC) in a major clinical trial. The present study investigated the economic impact of micafungin vs. LAmB in treating candidaemia and IC. A decision analytical model was constructed to capture downstream consequences of using micafungin or LAmB as primary definitive therapy. The main outcomes were treatment success and treatment failure due to mycological persistence, or death. Outcome probabilities were derived from key published sources. Resource used was estimated by an expert panel and cost inputs were from the latest Australian resources. The analysis was from an Australian hospital perspective. Sensitivity analyses using Monte Carlo simulation were conducted. Micafungin (AU61 426) had a lower total cost than LAmB (AU72 382), with a total net cost‐saving of AU10 957 per patient. This was primarily due to the lower cost associated with initial antifungal treatment and shorter length of stay for patients in the micafungin arm. Hospitalisation was the main cost driver for both arms. Results were robust over a wide range of variables. The uncertainty analysis demonstrated that micafungin had a 99.9% chance of being cost‐saving compared with LAmB. Micafungin was associated with cost‐saving relative to LAmB in the treatment of candidaemia and IC in Australia.